Universal conductance for the Anderson model - Oliveira, L. N.; Yoshida, M. [UNESP]; Seridonio, A. C. (IOP Publishing, 2010)
We discuss the thermal dependence of the zero-bias electrical conductance for a quantum dot embedded in a quantum wire, or side-coupled to it. In the Kondo regime, the temperature-dependent conductances map linearly onto the conductance for the symmetric Anderson Hamiltonian. The mapping fits accurately numerical renormalization-group results for the conductance in each geometry. In the side-coupled geometry, the conductance is markedly affected by a gate potential applied to the wire; in the embedded geometry, it is not. © 2010 IOP Publishing Ltd.
Keywords: Anderson Hamiltonian; Anderson models; Electrical conductance; Gate potentials; Kondo regime; Quantum Dot; Quantum wires; Renormalization group; Temperature dependent; Thermal dependences; Zero-bias; Wire; Computational geometry